Developing positive assertiveness - Lloyd, Sam R. (Crisp Pub. Menlo ParkUS, 1995)
Explains the difference between non-assertive, aggressive, and assertive behaviour styles. Shows how positive assertiveness can be learned; expressed in relation to personality type; and, improve relationship skills.